The experiences of students in disclosing their HIV positive status at the University of Limpopo, Turfloop Campus - Mampa, Seponono Raesibe (My University, 2015)
The purpose of this study was to determine the experiences of students in disclosing their HIV-positive status at the University of Limpopo, Turfloop Campus. A qualitative, descriptive, phenomenological design was used to explore, describe, and understand the experiences of the students with regard to the disclosure of their HIV-positive status. A group of 20 students who belonged to the support group were purposively sampled. Semi-structured interviews were conducted for data collection until saturation was reached. Data analysis was conducted according to Techs open-coding method. The study highlights the potential factors that might hinder access to HIV prevention, management, care, and support programmes. The findings reveal that there is a marked societal shift in the perception and understanding of HIV, resulting in disclosure being a less difficult responsibility. However, rejection by sexual partners has also been revealed. This rejection is one of the negative consequences that might hamper future disclosure. It is recommended that counsellors should be highly skilled in counselling HIV-positive people, especially about issues of disclosure. An HIV disclosure model will greatly support the work of these counsellors.
Thesis (MCur.) -- University of Limpopo, 2015
Keywords: HIV positive status; Student disclosure; College students -- Health and hygiene.; HIV positive persons -- South Africa -- Limpopo.